2021
DOI: 10.1186/s12889-021-11929-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis experiences from 50 hepatitis B patients in Chongqing, China: a qualitative study

Abstract: Background The aim of this study was to provide recommendations for reducing the impact of hepatitis B infection on patients with chronic hepatitis B by describing their experiences during the diagnosis process. Methods We conducted face-to-face interviews with 50 hepatitis B patients recruited by convenient sampling from an infectious diseases department of a teaching hospital in Chongqing, China from July to August 2019. Thematic analysis framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The current hepatitis control strategy in China places significant reliance on secondary care facilities for HBV detection on an ad hoc basis [ 45 ]. Previous studies have also identified that the dominant barriers to HBV detection in China are patients who report no or minimal physical complaints, as well as inadequate training and support for primary care practitioners [ 9 , 46 ]. The current study maximized the use of clinical information from text records and quantitative laboratory test parameters by utilizing the latest ML technologies to achieve precise detection of suspected cases across various clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The current hepatitis control strategy in China places significant reliance on secondary care facilities for HBV detection on an ad hoc basis [ 45 ]. Previous studies have also identified that the dominant barriers to HBV detection in China are patients who report no or minimal physical complaints, as well as inadequate training and support for primary care practitioners [ 9 , 46 ]. The current study maximized the use of clinical information from text records and quantitative laboratory test parameters by utilizing the latest ML technologies to achieve precise detection of suspected cases across various clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%